Pengembangan Sistem Informasi Portal Solo Photography Festival berbasis Website dengan Metode Agile Software Development - Nuryadi; Feri Efendi, Tino; Muslihah, Isnawati (LPPM ITB AAS Indonesia, 2023)
The Solo Photography Festival Portal Information System that has been running previously has many shortcomings, in terms of visitors and website administrators. System development is needed to overcome deficiencies and obstacles in managing the website. Therefore, maintenance is needed in a short time and does not affect the running system, through the development of the SDLC (Software Development Life Cycle) using the Agile Software Development method with the Scrum approach. The implementation of 6 product backlogs, 6 sprints, and daily meetings and demos really helped the effectiveness of system development. With this research, it is hoped that it can attract more visitors, especially SPF exhibitors to explore websites with better management and more attractiveness with the display of exhibition archives and other features